Factors associated with meeting the WHO physical activity recommendations in pregnant Colombian women - José Francisco López-Gil; Mikel Izquierdo; Antonio García-Hermoso; Alicia M. Alonso-Martínez; David Rincón-Pabón; Marco Antonio Morales-Osorio; Robinson Ramírez-Vélez (Scientific Reports, 2022)
Abstract In the absence of medical contraindications, physical activity (PA) can offer health maternal and fetal health outcomes during pregnancy. However, most pregnant women may not consider PA to be feasible, suitable and safe. Hence, it is essential to determine the prevalence of pregnant women who meet the PA recommendations and the possible factors associated with that meeting, since it might be important from the perspective of pregnant women's health. The aim of the present study was to establish the prevalence of meeting the World Health Organization PA recommendations for Colombian pregnant women, as well as possible factors that may be associated with meeting that recommendations. A cross-sectional study including representative data from the National Nutritional Situation Survey (2015) in Colombia was performed. Data were collected in 2015–2016. From an initial sample of 1140 Colombian pregnant women, 702 participants with complete data were included in the final analysis. PA was assessed by self-reported information through the long version of the International Physical Activity Questionnaire. Several potential factors were analysed according to four levels of the socioecological model: the individual, interpersonal, organizational and community levels. The prevalence of Colombian pregnant women who met with the PA recommendations was 7.5%. Indigenous and Mestizo pregnant women showed lower probabilities of meeting the PA recommendations [Indigenous: OR 0.05, 95% CI (0.01–0.18); Mestizo: OR 0.12, 95% CI (0.06–0.22)] than Afro-Colombian participants. Additionally, participants who lived near green and safe spaces for PA were more likely to meet the PA recommendations [OR 2.30, 95% CI (1.06–4.79)] than those who did not live near green areas. In conclusion, a low percentage of Colombian pregnant women met the new PA recommendations. The associations found according to race/ethnicity and living near green and safe areas underline the presence of fundamental disparities associated with meeting PA recommendations.